Meta Analysis: Effects of Household Size, Maternal Education, and Family Income on Stunting - Septa Decelita Wahyuni; Bhisma Murti; Rita Benya Adriani (Masters Program in Public Health, 2023)
Background: Nutrition is a requirement for every toddler. Inadequate nutritional intake will cause stunting problems. Stunting is a condition of failure to thrive in children where toddlers are shorter in age. This study aims to examine the effect of the number of family members, mother's education and family income on stunting by using meta-analysis. Subjects and Method: This was a systematic review and meta-analysis. Population was infants aged 6-59 months. Intervention: high number of family members, high mother's education, high family income. Comparison: low number of family members, low mother's education and low family income. Outcome: stunting. The online databases used are PubMed, Google Scholar, springerlink, and Science Direct with the keywords Stunting AND (“Family Size OR “Household Size”) AND (“Maternal Education” OR “Mother's Education”) AND “Wealth Status” OR “Household income”) AND “Cross sectional” AND aOR. There were 13 published cross-sectional studies from 2016-2022 that met the inclusion criteria. Analysis was performed using RevMan 5.4. Results: A meta-analysis was carried out on 13 articles with a cross-sectional study design originating from Ethiopia, Nigeria and Zambia and involving 63,888 aged 6-59 months. The results of the meta-analysis show that toddlers with a high number of family members have a risk of stunting 1.43 times compared to a low number of family members (aOR = 1.43; 95% CI = 1.17 to 1.75; p<0.001), toddlers with low maternal education can reduce stunting 0.65 times compared to mothers with high education (aOR= 0.65; 95% CI= 0.48 to 0.88; p= 0.005) and toddlers with low family income can reduce the risk of stunting 0.53 times compared to high family income (aOR= 0.53; 95% CI= 0.47 to 0.59; p<0.001). Conclusion: Toddlers with a high number of family members can increase the risk of stunting while high maternal education and low family income can reduce the risk of stunting. Keywords: number of family members, mother's education, family income, stunting Correspondence:Septa Decelita Wahyuni, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: septadeclita@gmail.com. Mobile: +6281373083322.